Lightweight aggregate concrete produced with crushed stone sand as fine aggregate. Issue 1 (1st January 2020) - Nassar, Roz-Ud-Din; Bhatti, Sheroz Saleem; Shahin, Mohamed; Hossain, Munemul; Slibi, Haitham Ahmad Al
Abstract: Lightweight aggregate concrete mixtures incorporating 0, 10, 20, and 30 weight percent replacement of normal-weight aggregate with lightweight aggregate and crushed stone as fine aggregate were tested at 7, 28, 56, and 90 days for various strength and durability characteristics of hardened concrete. Test results indicated that compressive, flexural, and split tensile strengths and static modulus of elasticity of concrete mixtures reduced with an increase in the percent replacement of normal-weight aggregate with lightweight aggregate. Furthermore, the volume of permeable voids and hence moisture sorption in lightweight aggregate concrete reduced as the lightweight aggregate content was increased pointing at the enhanced durability of the lightweight aggregate concrete mixtures. A significant reduction in dry density of hardened concrete was recorded due to the inclusion of lightweight aggregate in concrete mixtures. Considering the strength and reduction in dry mass, 20 wt.% replacement of normal-weight aggregate with lightweight aggregate is considered to be an optimum level. Reduced density of lightweight aggregate concrete mixtures is viewed as a major source of economical design of structural members as the lower concrete density will result into a reduction of self-weight of the structural members, which will allow the economical structural design of such members with smaller cross-sections. Test results of this work also showed the viability of 100% replacement of desert sand with crushed stone sand as fine aggregate towards the production of lightweight aggregate concrete.